Desenvolvimento de microcantilever funcionalizado com polímero condutor para a detecção de compostos orgânicos voláteis e umidade relativa - Steffens, Clarice (2012)
The great interest to develop microcantilevers sensors is due to several desirable properties, in particular the ability to adjust the size and structure, thus increasing the perspectives for the construction of new sensor systems. In this work, we developed functionalized microcantilever sensors with conducting polymers to detect relative humidity, volatile organic compounds and insect pheromones. The development was based on a systematic investigation, since the polymer synthesis and the film formation until the sensing step. For this purpose, we studied two treatments to clean the microcantilevers surfaces (plasma and piranha solution). Also, appropriate ways for the sensors functionalization were evaluated, using spin-coating and thermoelastic probe techniques. The polyaniline solutions were obtained by the in-situ and interfacial synthesis. This way, the doping, morphology and the polymer structure have been investigated by the AFM, UV-Vis, FTIR, diffraction and FE-SEM techniques, and likewise the film properties. It allowed us to optimize the preparation conditions of the polyaniline films on the surface of the microcantilevers sensors to detect relative humidity and volatiles. Also, it was possible to develop sensors with polyaniline thin films, capable to detect 1 ppmv of relative humidity, and this shows that they can be used to measure large limits of detection. Moreover, the functionalized microcantilevers sensors showed a fast response time, repeatability over several cycles and exhibited lifetime longer than 6 months. The coated microcantilevers sensors showed an excellent response to the volatile organic compounds (VOCs), indicating that the sensitive layer was xiv appropriate for detection of these volatiles. The sensitivity of these sensors at VOCs increased with the polarity, thus the methanol compound showed the greatest sensitivity. It was possible to detect and evaluate different concentrations of the pheromone 2-heptanone, at different temperatures. The microcantilever sensors response not only showed an excellent sensitivity, but also a fast response time. It was observed an excellent response to deflection of the microcantilever sensors when exposed to volatile during the banana ripeness.